(untitled) (Economics and region, 2018)
The article deals with the status of foreign direct investment into the national economy. The author researched the process of attracting foreign investment given the motivation of the investor and the country-recipient. It is proved the feasibility of the change of privatization paradigm to revitalize investment processes in Ukraine.